Influence of tibialis posterior muscle activation on foot anatomy under axial loading: A biomechanical CT human cadaveric study. Issue 4 (December 2017) - Dullaert, Koen; Hagen, Jennifer E.; Simons, Paul; Gras, Florian; Gueorguiev, Boyko; Richards, R. Geoff; Klos, Kajetan
Highlights: Effect weight bearing has on foot configuration investigated. Actuation of TP tendon does not reconstitute medial longitudinal arch integrity under weight bearing. Actuation of TP tendon does not correct hindfoot subluxation under weight bearing. Abstract: Background: Collapse of the medial longitudinal arch and subluxation of the subtalar joint are common occurrences in adult flatfoot deformity. Controversy exists about the role of the tibialis posterior (TP) tendon as first and/or essential lesion. Subtle changes in the foot configuration can occur under weight bearing. Purpose: This human cadaveric study is designed to investigate the effect that isolated actuation of the TP tendon has on the medial longitudinal arch and the hindfoot configuration under simulated weight bearing. Methods: A radiolucent frame was developed to apply axial loading on cadaveric lower legs during computer tomography (CT) examinations. Eight pairs of fresh-frozen specimens were imaged in neutral position under foot-flat loading (75 N) and under single-leg stance weight bearing (700 N) without and with addition of 150 N pulling force on the TP tendon. Measurements of subtalar joint subluxation, forefoot arch angle and talo-first metatarsal angle were conducted on each set of CT scans. Results: Subtalar subluxation, talo-first metatarsal angle and talo-navicular coverage angle significantly increased under single-leg stance weight bearing, whereas forefoot arch angle significantly decreased. Actuation of the TP tendon under weight bearing did not restore the forefoot arch angle or correct subtalar subluxation and talo-metatarsal angle. Conclusion: Significant effect that weight bearing has on the medial longitudinal arch and the subtalar joint configuration is demonstrated in an ex-vivo model. In absence of other medial column derangement, actuation of the TP tendon alone does not seem to reconstitute the integrity of the medial longitudinal arch or correct the hindfoot subluxation under weight bearing. Clinical relevance: The findings of this study together with the developed model for ex-vivo investigation provide a further insight in foot anatomy.